The prevalence of hepatic granulomas in chronic hepatitis C - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2004)
Objectives: Hepatic granulomas are not usual findings in chronic hepatitis C. A few studies addressing the frequency of hepatic granulomas in chronic hepatitis C reported it as less than 10%. The presence of it has been suggested to predict a favorable response to interferon treatment. Also, case reports described the development of hepatic granulomas after interferon treatment. In this study, we aimed to detect the prevalence of hepatic granulomas in chronic hepatitis C and to identify the causes other than chronic hepatitis C, if present, to search whether there is an association between the presence of granuloma and response to interferon treatment and also to see whether interferon leads to the formation of hepatic granulomas. Methods: Patients from 3 university clinics were included. All patients with chronic hepatitis C were determined. All patients with hepatic granulomas were screened for the other causes of hepatic granuloma with tuberculin skin test, chest X-ray and computed tomography, Venereal Disease Research Laboratory, and Brucella agglutination tests. The histologic assessment of liver biopsies was done by the same pathologist in each center. Results: A total of 725 liver biopsies of 605 patients with chronic hepatitis C were screened. In 8 patients, hepatic granulomas were detected in the initial liver biopsies. Four patients had repeat biopsies, and all had hepatic granulomas again. The prevalence of hepatic granulomas in patients with chronic hepatitis C was calculated as 1.3% (8 of 605) in reference to patient population. Presence or absence of hepatic granulomas was seemingly stable. All patients with hepatic granulomas had negative results of tuberculin skin test, Venereal Disease Research Laboratory, chest X-ray and computed tomography, and Brucella agglutination tests. All repeat biopsies were obtained after interferon ( ribavirin) in varying doses and duration. Four of 8 patients with hepatic granulomas were found to respond interferon therapy. No patient was found to develop hepatic granulomas after interferon therapy. Conclusion: Hepatic granulomas are a rare finding in HCV infection. The presence of it does not seem to predict the response to interferon therapy. The development of hepatic granulomas during interferon therapy is not usual.
Keywords: hepatic granuloma; chronic hepatitis C; interferon; LIVER-BIOPSY; INTERFERON; DIAGNOSIS